Impact of Nitrogen and Potash on the Incidence of Scirpophaga incertulas and Cnaphalocrocis medinalis and Yield of Rice - Chatterjee, Sitesh; Mondal, Palash (International Journal of Bio-resource and Stress Management, 2020)
The experiment was conducted at Rice Research Station, Chinsurah, West Bengal, India during June-November 2010, 2011 and 2012 to evaluate the different doses of nitrogen and potash fertilizers on the incidence of Scirpophaga incertulas and Cnaphalocrocis medinalis in Swarna (MTU 7029) variety. Among the three straight fertilizers, N was applied at three split doses while P2O5 and K2O were applied basally. Eight treatments with different doses of N:P2O5:K2O viz. 40:40:20, 40:40:40, 80:40:20, 80:40:40, 80:40:60, 120:40:40, 120:40:60 and 0:40:0 were laid out in RCBD with three replications. The observations on dead heart (DH), white ear head (WE) and leaf folded (LF) were noted down. The pooled data of three consecutive years revealed the lowest DH% and WE% in 80:40:40 (3.96% DH and 4.70% WE) while lower LF% was recorded in 80:40:60 (1.75%) and 80:40:40 (2.02%). Percent DH, WE and LF were comparatively higher in both 120:40:60and 120:40:40. However, the treatments supported higher plant height and tillers hill-1, panicles hill-1 and 1000 grain weight which resulted in the highest grain (4926 kg ha-1) and straw (6028 kg ha-1) yield in 120:40:60 followed by the treatment 80:40:60 with 4907 kg ha-1 and 5972 kg ha-1, respectively. The results reflected that higher pest damage due to N at the dose of 120 kg ha-1 could be compensated by K2O @ 60 kg ha-1 which boosted the yield. Based on benefit-cost ratios, the treatments 80:40:40 and 80:40:60 proved cost effective.